Suggestions and debates : the national integration of European working classes (1871-1914) : exploring the causal configuration - van der Linden, Marcel ([Cambridge] : [University Press], 1988)
Bibliotheek François Vercammen
Overdruk van International Review of Social History, vol. 33 (1988), nr. 3
Engels
Brochure
Keywords: arbeidersemancipatie; Europa